2018
DOI: 10.1016/j.ejor.2017.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Insurance with multiple insurers: A game-theoretic approach

Abstract: This paper studies the set of Pareto optimal insurance contracts and the core of an insurance game. Our setting allows multiple insurers with translation invariant preferences. We characterise the Pareto optimal contracts, which determines the shape of the indemnities. Closed-form and numerical solutions are found for various preferences that the insurance players might have. Determining associated premiums with any given optimal Pareto contract is another problem for which economic-based arguments are further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 50 publications
(69 reference statements)
1
30
0
Order By: Relevance
“…Previous studies that used industry data for insurance and risk management analysis can be found in Refs. [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] . Details on other researched works on the subject and relevant literature can be found in Refs.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies that used industry data for insurance and risk management analysis can be found in Refs. [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] . Details on other researched works on the subject and relevant literature can be found in Refs.…”
Section: Datamentioning
confidence: 99%
“…Details on other researched works on the subject and relevant literature can be found in Refs. [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] . There are several lessons other businesses can learn from insurance sector dataset especially in terms of business continuity, business resilience, strategic innovation, and sustainable survival during the global financial crisis.…”
Section: Datamentioning
confidence: 99%
“…Likewise, the data analysis can allow for measurement of insurance firms competitiveness and detect systemic risk which may disrupt the financial industry. Research questions can be posed as in previous studies [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , which in turn can lead to inferential statistics, which when interpreted can inform the development of policies and strategic actions for the competitiveness and innovation of insurance industry. The uniqueness of this data is its focus on insurance business as risky which is an area where Solvency II concentrates on as a risk-based approach to prevent the failure of insurance firms.…”
Section: Datamentioning
confidence: 99%
“…If we remove the assumption of comonotonicity, it will be challenging to find an explicit optimal allocation even with value at risk (VaR) and for identical weights under heterogeneous beliefs; see Embrechts et al (2018b). See Boonen et al (2018), Asimit andZhuang et al (2016) for more discussions on the use of comonotonic allocations in risk-sharing games and insurance. Under the assumption of comonotonicity, we are able to find optimal allocations for risk sharing with general distortion risk measures and characterize the set of Pareto-optimal allocations.…”
Section: Introductionmentioning
confidence: 99%